Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Suku Dinas Perumahan Rakyat Dan Kawasan Permukiman Walikota Jakarta Barat - Lisa Banowati; Ratih Hastasari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
In a company, of course, when carrying out their work, employees must have work motivation, this can encourage employees to create work enthusiasm. Apart from work motivation, there are things that can trigger employee performance, namely the work environment. This work environment is what every company owner needs to pay attention to, so that it can create a feeling of comfort and make employees work more optimally. This research aims to determine whether there is an influence between work motivation and the work environment on employee performance in the public housing sub-department and the West Jakarta mayor's residential area. This research uses quantitative research methods, and the sample size is 30 employees. Data collection is by distributing questionnaires. Data testing techniques in this research use validity tests, reliability tests, classical assumption tests, hypothesis tests, and coefficient of determination tests. The research results show that: 1) Work motivation partially has a significant effect on employee performance, 2) The work environment partially has a significant effect on employee performance, 3) Work motivation and the work environment simultaneously have a significant effect on employee performance.